Nilai-Nilai Kerukunan dalam Naskah Serat Waosan Puji - Zakiyah Zakiyah (Jurnal Lektur Keagamaan, 2012)
This paper discusses a manuscript entitled Serat Waosan Puji, a collection of the Widya Budaya Library of the Yogyakarta Kingdom. The manuscript which is in a good condition and readable consists of several texts. They tell about do’a (prayer), pillar of faith, pillar of Islam, theology, name of verses of al-Qur’an, Ki Purwadaksina’s teaching, Serat Nitisruti, and Serat Nitipraja. Meanwhile, the teaching of harmony is stated in three pupuh (chapters) dhandhanggula of Ki Purwadaksina’s teaching, Serat Nitisruti, and serat Nitipraja.